If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10p-3(6-6p)=6(p-6)-6
We move all terms to the left:
-10p-3(6-6p)-(6(p-6)-6)=0
We add all the numbers together, and all the variables
-10p-3(-6p+6)-(6(p-6)-6)=0
We multiply parentheses
-10p+18p-(6(p-6)-6)-18=0
We calculate terms in parentheses: -(6(p-6)-6), so:We add all the numbers together, and all the variables
6(p-6)-6
We multiply parentheses
6p-36-6
We add all the numbers together, and all the variables
6p-42
Back to the equation:
-(6p-42)
8p-(6p-42)-18=0
We get rid of parentheses
8p-6p+42-18=0
We add all the numbers together, and all the variables
2p+24=0
We move all terms containing p to the left, all other terms to the right
2p=-24
p=-24/2
p=-12
| -x-8=4x+17 | | 8x-(2x+9)=8x-13 | | 17x+3-12x=8x+9 | | 7-3x=28-4x | | -10=-3t+2 | | 8x+3x+3-2=90 | | 16-7x=5x-8 | | X+1-3x=9 | | 1/2(4y-8)=4 | | 5x+3(x-4)=8x-15 | | 2(3x−4)=3+6x | | 4x+10=46-2x | | 2(3x−4)=3+6x. | | 6x-8(2x-4)=46 | | -4-6x=6(3-x)-5x | | 5x10+10=3x-12 | | 9m+10=46 | | -14+6=-2(x+6) | | 5=6(y-2)-1 | | 12m-27=7m+43 | | 17+4=-3(2x-7) | | 4x+1.4=6.2 | | 4x-17=-11 | | 9x-8=5x-10 | | 2.3=(t-1.8)/2 | | -6(n-6)=12 | | x/5+x/8=13/14 | | 4(2x+9)=-40+44 | | 3n+1=-6-4n | | 5x–45=–10 | | -4(v-75)=-48 | | 2(t−5)=48 |